Women Objectification in The Testaments by Margaret Atwood (2019) - Aisyah Amilatul Quran; Desvalini Anwar (English Language and Literature, 2020)
AbstractThe purpose of this analysis is to expose the issue of women objectification in novel The Testaments (2019) by Margaret Atwood. The issue of women objectification refers to the various ways men objectify and subordinate women’s characters in every aspect of women’s life. This analysis focuses on men’s actions in restricting women’s life choices and using religion as a shield to regulate women’s body. This analysis is text-based interpretation based on the concept of women objectification theory proposed by Martha Nusbaum. This analysis uses fictional devices such as character, plot (conflict) and setting that contribute in revealing the issue. The result of the study reveals the way men objectify women is done two ways; they are choice restriction and religion distortion.